The influence of Bank Syariah Indonesia's brand logo on brand image: comparison between brand personality and halal brand personality - Anya Safira; Mohammad Anugerah Amiluhur (Faculty of Business & Economics, Universitas Islam Indonesia, 2021)
Purpose: The main purpose of this study is to investigate the effect of the brand logo on brand image, with the mediation of brand personality and brand familiarity.Methodology: Questionnaires were distributed online to users of Bank Syariah Indonesia throughout Indonesia and obtained data from 294 respondents that can be processed. The data processing method used was structural equation modeling.Findings: This study found an indirect positive influence between brand logo and brand image with the mediation of brand personality and brand familiarity. Although the Bank Syariah Indonesia brand logo has a positive effect on halal brand personality, halal brand personality does not mediate the relationship between the brand logo and the brand image of Bank Syariah Indonesia.Originality: This originality offered by this research is by comparing the constructs of brand personality with halal brand personality.Research limitations: Limitations of this research include uneven distribution of respondents and limited previous literature regarding halal brand personality.Practical implications: The findings of this research can provide insights for Islamic banks, especially Bank Syariah Indonesia, to develop their communication and branding strategies.